Ewa Lipska as a political writer - Arkadiusz Morawiec (Przestrzenie Teorii)
The article deals with the image of Ewa Lipska as a political writer, a committed person, and also discusses her attitude to Poland. In the studies conducted so far this aspect of her work was merely indicated, and also was sometimes a subject of manipulation. From the point of view of today it can be clearly seen that, along with the “private” motif, it crucially co-creates Lipska’s oeuvre. It is also important that the writer has expressed her social and political commitment not only in poetry (which she has published from 1961) and poetic drama (Nie o śmierć tutaj chodzi, lecz o biały kordonek [Death is Not at Stake, But the White Cord] of 1981), but also, and even most of all, in her prose (which so far has been neglected by researchers), especially Żywa śmierć [Living Death] (2009), Sefer (2009) and the columns published since 2004 in the “Kraków” monthly.